Pepsinogen II Can Be a Potential Surrogate Marker of Morphological Changes in Corpus before and after H. pylori Eradication. (17th June 2014) - Massarrat, Sadegh; Haj-Sheykholeslami, Arghavan; Mohamadkhani, Ashraf; Zendehdel, Nasrin; Aliasgari, Ali; Rakhshani, Naser; Stolte, Manfred; Shahidi, Seyed Mehdi
Abstract : Background. The aim of this investigation is to study the relationship between gastric morphology and serum biomarkers before and after Helicobacter pylori eradication. Methods . First-degree relatives of gastric cancer patients underwent gastroscopy before and 2.5 years after H. pylori eradication. The morphological changes in two categories (normal to mild and moderate to severe) were compared with level of pepsinogens I and II before eradication (n = 369 ), after eradication (n = 115 ), and in those with persistent infection (n = 250 ). Results : After eradication, pepsinogen I decreased to 70% and pepsinogen II to 45% of the previous values. Unlike pepsinogen II and pepsinogen I to II ratio that were affected by the severity of inflammation and atrophy in corpus in all groups, pepsinogen I generally did not change. After eradication, subjects with high mononuclear infiltration in corpus had lower pepsinogen I (54 versus 77.1  μ /mL), higher pepsinogen II (9.4 versus 6.9  μ /mL), and lower ratio (7.9 versus 11.6) than those without (P < 0.05 ). Conclusion . Pepsinogen II is a good marker of corpus morphological changes before and after H. pylori eradication.